Low FEV1, smoking history, and obesity are factors associated with oxygen saturation decrease in an adult population cohort - Vold,Monica Linea; AasebÃ¸,Ulf; Melbye,Hasse (International Journal of Chronic Obstructive Pulmonary Disease, 2014)
Monica Linea Vold,1,3 Ulf Aasebø,1,2 Hasse Melbye3 1Department of Respiratory Medicine, University Hospital of North Norway, 2Department of Clinical Medicine, 3Department of Community Medicine, University of Tromsø, Tromsø, Norway Background: Worsening of pulmonary diseases is associated with a decrease in oxygen saturation (SpO2). Such a decrease in SpO2 and associated factors has not been previously evaluated in a general adult population. Aim: We sought to describe SpO2 in a sample of adults, at baseline and after 6.3 years, to determine whether factors predicting low SpO2 in a cross-sectional study were also associated with a decrease in SpO2 in this cohort. Methods: As part of the Tromsø Study, 2,822 participants were examined with pulse oximetry in Tromsø 5 (2001/2002) and Tromsø 6 (2007/2008). Low SpO2 by pulse oximetry was defined as an SpO2 ≤95%, and SpO2 decrease was defined as a ≥2% decrease from baseline to below 96%. Results: A total of 139 (4.9%) subjects had a decrease in SpO2. Forced expiratory volume in 1 second (FEV1) <50% of the predicted value and current smoking with a history of ≥10 pack-years were the baseline characteristics most strongly associated with an SpO2 decrease in multivariable logistic regression (odds ratio 3.55 [95% confidence interval (CI) 1.60–7.89] and 2.48 [95% CI 1.48–4.15], respectively). Male sex, age, former smoking with a history of ≥10 pack-years, body mass index ≥30 kg/m2, and C-reactive protein ≥5 mg/L were also significantly associated with an SpO2 decrease. A significant decrease in FEV1 and a new diagnosis of asthma or chronic obstructive pulmonary disease during the observation period most strongly predicted a fall in SpO2. A lower SpO2 decrease was observed in those who quit smoking and those who lost weight, but these tendencies were not statistically significant. Conclusion: A decrease in SpO2 was most strongly associated with severe airflow limitation and a history of smoking. Smoking cessation and reducing obesity seem to be important measures to ...